2013
DOI: 10.1002/qua.24443
|View full text |Cite
|
Sign up to set email alerts
|

Geometry, stability, and isomerization of B n N2 (n = 1−6) isomers

Abstract: We perform a systematic study on the geometry, stability, nature of bonding, and potential energy surface of low-lying isomers of planar and cyclic B n N 2 (n ¼ 1À6) at the CCSD(T)/ 6-311þG(d)//B3LYP/6-311þG(d) level. B n N 2 (n ¼ 2À4) clusters are structurally similar to pure boron clusters. The evolution of the binding energy per atom, incremental binding energy, and second-order difference of total energy with the size of B n N 2 reveals that the lowest energy isomer of B 3 N 2 has high stability. B 5 N 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…It is interesting to note the increase in the B-B bond lengths in the B 3 32 The B 3 N 2 cluster was studied computationally, suggesting that the N atoms also insert into the B-B bonds and disrupt the B 3 triangle. 33 However, a previous theoretical study showed that P 2 B n clusters exhibit global minimum structures similar to the corresponding Bi 2 B n clusters studied currently. 34 A recent study of Bi 2 Al n clusters showed that they all have three-dimensional structures due to the weak Al-Al bonds.…”
Section: Comparison Of the Structures Of B-bi And Other B-group-v Binmentioning
confidence: 54%
See 1 more Smart Citation
“…It is interesting to note the increase in the B-B bond lengths in the B 3 32 The B 3 N 2 cluster was studied computationally, suggesting that the N atoms also insert into the B-B bonds and disrupt the B 3 triangle. 33 However, a previous theoretical study showed that P 2 B n clusters exhibit global minimum structures similar to the corresponding Bi 2 B n clusters studied currently. 34 A recent study of Bi 2 Al n clusters showed that they all have three-dimensional structures due to the weak Al-Al bonds.…”
Section: Comparison Of the Structures Of B-bi And Other B-group-v Binmentioning
confidence: 54%
“…29 There have been few experimental studies of boron clusters doped by group V elements except B n N − (n = 1-3). [30][31][32] Computational studies have been reported on B n N 2 (n = 1-6) and B n P 2 (n = 1-7) clusters, 33,34 as well as a joint experimental and theoretical study on the isoelectronic Bi 2 Al n (n = 1-4) clusters. 35 Extending our prior study on the bismuth-boron double bond and triple bond in Bi 2 B − and BiB 2 O − , 9 respectively, here we report an investigation on a series of di-bismuth boron clusters, Bi 2 B n − (n = 2-4), using high resolution PE imaging and quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated (BN) 2 and (BN) 3 species, as well as higher oligomers, have been the subjects of numerous computational investigations; [69][70][71][72][73][74] monomeric BN has also been studied extensively. [75][76][77] The isolated systems are not the focus of the present study, however, results for the isolated species are reported for the corresponding isomers considered in the complexes for completeness.…”
Section: Resultsmentioning
confidence: 99%